Djurhälsopersonalens anmälningsplikt på smådjurskliniker - Örnsjö, Martina (2016)
Since 2010 all animal health personnel have a duty to report any suspicion that an animal is not treated in accordance with animal welfare legislations. The number of such reports from animal clinics is low and the reasons for this are many. Many of the animal health personnel feel insecure when they should submit a report of a pet owner and do not feel sure how to proceed. The available information about animal health personnel duty to report is scarce. This study aimed to investigate whether the occurence of reports differed depending on the animal clinic size, the presence of developed procedures and the animal health personnel feelings and knowledge about their duty to report any non-compliance with animal welfare legislation. Through an online survey emerges here that a total of 41 % of the respondents workplaces did not have developed standard procedures for reporting. Only 22 % said that they felt sure about how to proceed to report and only 16 % that they knew when it was motivated to report, despite that 90 % of the respondents said that they knew about their duty. A total of 35 % of the respondents informed that they had report an owner for non-compliance with animal welfare legislation, of these 58 % were vets. No significant difference could be interpreted on the basis of respondents workplace size and number of reports, but an impression of a connection between the clinics with routines and the animal health personnel sense of when it is appropriate to report an owner could be considered. Based on literatur and research, suggestions for how small animal clinics may draw up guidelines to increase the awareness to the animal health personnel about how and when to report an owner for non-compliance with animal welfare legislation presents. Also a proposed about a direction guideline from Jordbruksverket is brought up with the expectation to make the animal health staff feel safer when to report a owner. The link between violence against animals and violence against humans i also discussed, where the study points out the importance of animal health personnel to stop and prevent both animals and people in distress, when, for example, animal cruelty can be a clear marker for family violence.